Biocompatible Glasses From Bone Regeneration to Cancer Treatment - Marchi, Juliana; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book focuses on the applications of bioglasses in the biomedical field. It starts with the history and evolution of bioglasses before moving on to the structure and percolation theory, and lastly investigating their current and potential future applications in various fields including dentistry, tissue engineering, bone regeneration, ophthalmology, and drug delivery. The chapters were written by a team of international experts in the field and will be of great interest not only to material scientists, but also to medical doctors and other health sector professionals.
Introduction -- History of Bioglasses -- Structure and percolation in Bioglasses -- Bioglasses for bone regeneration -- Biological response of bioglasses -- Bioglasses and Angiogenesis -- Bactericide Effect of Bioglasses -- Computational simulation of Bioglasses -- Bioglasses, tissue engineering and cells -- Bioglasses and drug delivery -- Bioglasses applied to dentistry -- Bioglasses applied to ophthalmology -- Bioglasses for cancer treatment -- A future perspective for Bioglasses.
Keywords: Biomaterials; Ceramic materials; Building materials; Biomaterials; Ceramics; Structural Materials